The flies of the family Hybotidae (Diptera, Empidoidea) collected during the Boyekoli Ebale Congo 2010 Expedition in Democratic Republic of Congo - Grootaert, Patrick; Shamshev, Igor (Zootaxa, 2013)
Thirty-two species of Hybotidae (Diptera: Empidoidea) were collected during the Boyekoli Ebale Congo 2010 Expedition that took place in the Democratic Republic of Congo along the Congo River between Kisangani and Bumba. Only four species were known previously. Here we present new records for Syndyas crisis Garrett Jones, 1940 and Crossopalpus aenescens (Wiedemann, 1830). In addition Syneches elevatus Bezzi, 1908 and Crossopalpus quadrispina (Collart, 1934) are re-described based on the type material as well as on new material. Elaphropeza ghesquierei (Collart, 1934) and E. plagiata (Bezzi, 1908) were not found during the expedition, but are also re-described. Twenty-five species are described as new to science: Crossopalpus yaekela sp. nov., Drapetis congoensis sp. nov., D. yaekelaensis sp. nov., D. zamba sp. nov., Elaphropeza angulata sp. nov., E. baeloi sp. nov., E. congoensis sp. nov., E. excavata sp. nov., E. furcata sp. nov., E. incerta sp. nov., E. infuscata sp. nov., E. interrupta sp. nov., E. juakalyi sp. nov., E. kona sp. nov., E. laudisoitae sp. nov., E. mai sp. nov., E. monoseta sp. nov., E. motane sp. nov., E. moyindo sp. nov., E. nuda sp. nov., E. yaekela sp. nov., E. zamba sp. nov., Stilpon congoensis sp. nov., S. variabilis sp. nov. and Syndyas zamba sp. nov. A species of Drapetis and Crossopalpus recorded from females only are diagnosed, but not named.